2010
DOI: 10.1115/1.4000729
|View full text |Cite
|
Sign up to set email alerts
|

Loading Analysis on the Thread Teeth in Cylindrical Pipe Thread Connection

Abstract: This paper presents a new analytical method that can calculate the load distribution on the thread teeth in cylindrical pipe threaded connection. The new method was developed by analyzing each male and female thread tooth from the connection on the basis of elastic mechanics. By using this method, the load distribution on each thread tooth can be calculated with the tightening torque and thread numbers. By applying the new method on the sample of API 88.9 mm round threaded connection, the obtained results show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 14 publications
1
14
0
Order By: Relevance
“…The bolt preload representation of screw fastening used in this study was found to produce results similar to a study by Gefen (2002) and to the analytical models of Grewal et al (1997) and Chen et al (2010b). Screw tightening results in compression of the bone against the plate; this compression increases the proportion of load taken in the vicinity of the first thread compared to pull-out style loading.…”
Section: Discussionsupporting
confidence: 63%
“…The bolt preload representation of screw fastening used in this study was found to produce results similar to a study by Gefen (2002) and to the analytical models of Grewal et al (1997) and Chen et al (2010b). Screw tightening results in compression of the bone against the plate; this compression increases the proportion of load taken in the vicinity of the first thread compared to pull-out style loading.…”
Section: Discussionsupporting
confidence: 63%
“…Parametric analyses and comparison with known analytical and experimental results revealed that stiffening could considerably reduce the stress concentrations. Chen et al [331] proposed a new analytical method for load distribution on the thread teeth in a cylindrical pipe threaded connection. The results showed that the load was concentrated mainly on the last 4-5 threads.…”
Section: Tubular Jointsmentioning
confidence: 99%
“…For threads failure of pipeline structures, He et al [ 13 ] presented a non-contact detecting method for oil tube thread, in which, the optical techniques and image processing techniques were employed to measure the physical dimensions of the tube thread and give further analysis. Chen et al [ 14 ] presented a new analytical method that can calculate the load distribution on the thread teeth in cylindrical pipe threaded connection by analyzing each male and female thread tooth from the connection on the basis of elastic mechanics.…”
Section: Introductionmentioning
confidence: 99%